One beetle too many eaudiobook - Lasky, Kathryn (Recorded Books Inc., 2010)
A lively exploration into the life of Charles Darwin, One Beetle Too Many recounts both Darwin's childhood and his time on the Beagle as a naturalist. This adventurous tale explores Darwin's discoveries in geology, paleontology, and animal anatomy that led to his famous theory of evolution.